The true art of the tax deal: Evidence on aid flows and bilateral double tax agreements - Julia Braun; Martin Zagler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
Out of a total of 2,976 double tax agreements (DTAs), some 60% are signed between a developing and a developed economy. As DTAs shift taxing rights from capital importing to capital exporting countries, the prior would incur a loss. We demonstrate in a theoretical model that in a deal one country does not trump the other, but that the deal must be mutually beneficial. In the case of an asymmetric DTA, this requires compensation from the capital exporting country to the capital importing country. We provide empirical evidence that such compensation is indeed paid, for instance in the form of bilateral official development assistance, which increases on average by six million US in the year of the signature of a DTA.
urn:nbn:de:bsz:180-madoc-421628
Keywords: K33; F53; H25; H87; D82; 330; developing countries; foreign aid; double taxation agreements